Community participation in waste management - Lidia Br Tarigan; Yuanita C. Rogaleli; Ferry W.F Waangsir (International Journal of Public Health Science (IJPHS), 2020)
Improper management of waste can be a source of health and environmental problems. Community participation contributes to effective waste management. The study was aimed at analyzing community participation in waste management at Liliba Village in Kupang City. This research is an analytic study with cross sectional study approach. The population was the entire population of Liliba Village in Kupang City. There were 133 respondents participated in this study. The data were analyzed using the structural equation model test. Education and occupation had strong correlation and significant influence to community participation. Community participation had strong relation and significant effect on waste production. Population had weak correlation and insignificant effect on waste production. It is recommended that interventions should be done for invalid indicator such as of waste utilization in the form of counseling or training on waste recycling.